Disability and information technology : a comparative study in media regulation - Varney, Eliza, 1978-; Cambridge eBooks (Cambridge : Cambridge University Press, 2013)
Disability and Information Technology examines the extent to which regulatory frameworks for information and communication technologies (ICTs) safeguard the rights of persons with disabilities as citizenship rights. It adopts a comparative approach focused on four case studies: Canada, the European Union, the United Kingdom and the United States. It focuses on the tension between social and economic values in the regulation of ICTs and calls for a regulatory approach based on a framework of principles that reflects citizenship values. The analysis identifies challenges encountered in the jurisdictions examined and points toward the rights-based approach advanced by the UN Convention on the Rights of Persons with Disabilities as a benchmark in protecting the rights of persons with disabilities to have equal access to information. The research draws on a wealth of resources, including legislation, cases, interviews, consultation documents and responses from organisations representing persons with disabilities.
1. The regulation of ICTs for the pursuit of citizenship rights -- 2. Case study: Canada -- 3. Case study: the European Union -- 4. Case study: the United Kingdom -- 5. Case study: the United States of America -- 6. Lessons to be learnt? : Reflection on the case studies.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: People with disabilities -- Information techology -- Case studies; People with disabilities -- Services for -- Data processing -- Case studies; Computers and people with disabilities -- Case studies; People with disabilities -- Legal status, laws, etc. -- Case studies; Mass media -- Law and legislation -- Case studies; Libraries and people with disabilities -- Case studies; Electronic books